Sistema de aquisição de dados para o estudo do movimento: uso de sequência de ensino investigativa - Marcelino, Daniela (2019)
This work proposes an educational product for the study of the movement of an object using a data acquisition system. The main objective is to develop an Investigative Teaching Sequence composed of a series of experimental activities for movement analysis. The experimental activities use a data acquisition system that collects position values as a function of time of an object using ultrasonic sensor and Arduino platform. The data acquisition system proved to be a versatile, accurate, low cost and easy to build learning tool. In addition, it enables the study of the objects with constant velocity, constant acceleration and oscillatory motion. An Investigative Teaching Sequence was applied to students from two classes of the 1st year of public high schools in western Paraná during the first semester of 2019. A pre and post test was used to evaluate the development of the acquired knowledge. The results of this analysis show that the learning objectives have been achieved. This educational product aims to make the classes more attractive and differentiated, leading to an assimilation of prior and scientific knowledge through the application of the Meaningful Learning methodology. Theory and practice together facilitate an easier understanding of physical concepts, so it is expected that this educational product will be an important tool for the teaching of physics.